Prevalence of HPV Infection in Racial-Ethnic Subgroups of Head and Neck Cancer Patients - Ragin, Camille; Liu, Jeffrey C; Jones, Gieira; Shoyele, Olubunmi; Sowunmi, Bukola; Kennett, Rachel; Groen, Harry J M; Gibbs, Denise; Blackman, Elizabeth; Esan, Michael; Brandwein, Margaret S; Devarajan, Karthik; et al. (Carcinogenesis, 2017)
The landscape of HPV infection in racial/ethnic subgroups of head and neck cancer (HNC) patients has not been evaluated carefully. In this study, a meta-analysis examined the prevalence of HPV in HNC patients of African ancestry. Additionally, a pooled analysis of subject-level data was also performed to investigate HPV prevalence and patterns of p16 (CDNK2A) expression amongst different racial groups. Eighteen publications (N = 798 Black HNC patients) were examined in the meta-analysis, and the pooled analysis included 29 datasets comprised of 3,129 HNC patients of diverse racial/ethnic background. The meta-analysis revealed that the prevalence of HPV16 was higher among Blacks with oropharyngeal cancer than Blacks with non-oropharyngeal cancer. However, there was great heterogeneity observed among studies (Q test P<0.0001). In the pooled analysis, after adjusting for each study, year of diagnosis, age, gender and smoking status, the prevalence of HPV16/18 in oropharyngeal cancer patients was highest in Whites (61.1%), followed by 58.0% in Blacks and 25.2% in Asians (P<0.0001). There was no statistically significant difference in HPV16/18 prevalence in non-oropharyngeal cancer by race (P=0.682). With regard to the pattern of HPV16/18 status and p16 expression, White patients had the highest proportion of HPV16/18+/p16+ oropharyngeal cancer (52.3%), while Asians and Blacks had significantly lower proportions (23.0% and 22.6%, respectively) [P <0.0001]. Our findings suggest that the pattern of HPV16/18 status and p16 expression in oropharyngeal cancer appears to differ by race and this may contribute to survival disparities.